34.8k views
4 votes
Y = 4x + 23 y = 2x + 9

1 Answer

4 votes

Question:

Solve the following linear system of equations:

y = 4x + 23

y = 2x + 9 ​

Solution:

Lets denote the above equation by:

y = 4x + 23 EQUATION 1

y = 2x + 9 EQUATION 2

If we substitute equation 2 ( the y ) in equation 1 we obtain:

2x +9 = 4x +23

solve for x:

2x-4x = 23-9

this is equivalent to:

-2x = 14

thus:

x = -7.

Now, to obtain y, replace x = -7 in equation 2:

y = 2(-7)+9 = -14+9 = -5

then we can conclude that the solution of this system of linear equations is:

x = -7

y = -5

User Snctln
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.